COVID-19 impact on B2B e-commerce: A multi-group analysis of sports and surgical SME's - Arsalan Hussain; Arfan Shahzad; Rohail Hassan; Shivan A. M. Doski (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The COVID-19 has forever changed the way firms use digital solutions for their B2B ecommerce activities. During this pandemic, only those industries are surviving, which have shifted their business model to online. Most of the counties' SME growth is badly affected by the COVID-19. Business-to-business e-commerce (B2B) is essential for a rapidly changing business environment and increases SME's overall performance. The study aims to explore the influence of technological (relative advantage and technology readiness), organizational (cost of adoption and top management support), and environmental (government support and competitive pressure) factors of the technological, organizational, and environmental (TOE) model on B2B e-commerce. The research framework was developed based on diffusion of innovation (DOI) theory and the TOE model. The research collects data from two heterogeneous groups sports and surgical. The 500 questionnaires were distributed to top and middle-level managers of Pakistan's manufacturing SMEs. Thus, 262 were returned. The study applies multi-group analysis by using the SmartPLS 3.3.2 to investigate the hypothesized relationships. The result shows that technological factors have a significant positive relationship with B2B e-commerce in sports and surgical SMEs. However, competitive pressure as an environmental factor differs in sports and surgical SMEs to use B2B e-commerce. The study provides theoretical and practical implications. The study helps SME managers and practitioners in understanding the underlying factors for the successful implementation of e-commerce.
Keywords: 330; relative advantage; cost of adoption; top management support; technologyreadiness; competitive pressure; government support; small and medium enterprises